PERAN DA’I DALAM MENINGKATKAN MOTIVASI MASYARAKAT DI JORONG LANDAI KECAMATAN HARAU KABUPATEN 50 KOTA - Nofria MetaSari; Tomi Hendra (Universitas Pahlawan Tuanku Tambusai, 2022)
Da’wah to the community is very important because it is an effort to invite people to do good and prevent people from doing bad things. Congregational prayer is an obligation that must be carried out by a muslim when he has reached puberty and has reason. But there are still people who do not pray in congregation. The role of the da’i in the community in understanding religious values. This research is motivated by the role of da’i in increasing the motivation of the people of Jorong Landai. Landai village is one of the villages that is still lacking in understanding and religious values, this can be seen in the implementation of congregational prayers, the lack of public understanding about praying in congregation, many of the people who do not pray in congregation, people are busy with business wordly, such as work, and so on. This study uses a qualitative method with descriptive qualitative approach. Descriptive qualitative research is a technique of collecting and analyzing data, whether in the form of pictures, words, or events. Data collection techniques used are observation, interviews, and documentation. The result of the study are the role of the preacher in increasing the motivation of the community in Jorong Landai, Harau district, 50 City, using approaches, among others, namely, first: by using real actions by providing an understanding of congregational prayers accompanied by actions by inviting prayers in congregation at the mosque. Second, the preacher becomes a good role model for the community who can bring change for the community to the right path. Third, with a wise approach to the community by using a good way. Fourth, the approach taken to the community by using patience in providing advice to the community. Keywords: Dai’s Role, Congregational Prayer.